Proceedings of the 36th International Spring Seminar on Electronics Technology 2013
DOI: 10.1109/isse.2013.6648283
|View full text |Cite
|
Sign up to set email alerts
|

Ink-jet printed strain sensor on polyimide substrate

Abstract: This paper describes a method for measuring strain on a specimen with flexible strain sensor. The sensor is made by ink-jet printing of silver ink on polyimide substrate, in that manner providing a combination of electrical conductivity and mechanical flexibility. When a force is applied on the free end of cantilever beam, three different strain gauges are used to measure flex of the beam. The gauge is taped at the fixed end of the beam, on the top side. To determine the strain, it requires accurate measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Design of printed strain gages in this paper is improved compared to the design presented in our previous research [15], by increasing the length of the end loop. Proposed length of strain gage end loop is five times longer than grid track width.…”
Section: Strain Gages Fabricationmentioning
confidence: 95%
“…Design of printed strain gages in this paper is improved compared to the design presented in our previous research [15], by increasing the length of the end loop. Proposed length of strain gage end loop is five times longer than grid track width.…”
Section: Strain Gages Fabricationmentioning
confidence: 95%
“…As mentioned earlier, the dielectric constants of the substrate and air tend to be different, so waves propagate in a nonuniform medium. When the antenna is bent, the increase in dielectric constant is related to the decrease in thickness [39]. In conclusion, it is concluded that the bending behavior of rectangular patch antennas is the result of a combination of the bending axis, electromagnetic properties, and mechanical properties of the antenna assembly.…”
Section: Dbending Strain Experimentsmentioning
confidence: 85%
“…The performances of the resulting strain sensor were electromechanically characterized using a homemade set-up which is described in [9] and shown in Fig.5.…”
Section: Caracterisationmentioning
confidence: 99%